Synthesis and Anti-inflammatory Activity of Steroidal Isoxazoles - Pathak, Devender; Paul Jindal, Dharam (Asian Journal of Chemistry, 2010)
The steroidal isoxazoles, 4-aza-5α-cholestano [3,2-c] isoxazole (2), 4-aza-5α-androstano [3,2-c] isoxazol-17β-yl acetate (4) and 17a-aza-Dhomo-5-androsteno [17,16-c] isoxazol-3β-yl acetate (6) have beenprepared and screened for their biological activity. The Compound 2(ED50 = 5.67 mg/kg), Compound 4 (ED50 = 2.97 mg/kg) and Compound 6(ED50 = 11.00 mg/kg) were found to be potent anti-inflammatory agents.